Pharmaceutical Care in the Unified Health System – Profile and Federal Financing - Lopes Medeiros Simone, Adriane; Freitas Saldanha, Tainá; Oliveira de Melo, Daniela (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2025)
Introduction: In June 2024, the National Guidelines for Pharmaceutical Care in the Unified Health System (Sistema Único de Saúde, SUS) were published. Their implementation requires the engagement of professionals and the availability of resources to develop and consolidate this practice in healthcare settings. Objective: To characterize the profile and federal financing for outpatient pharmaceutical care in SUS. Methods: Data from 2022 and 2023 from SUS systems were used to evaluate clinical assistance services (CAS) and technical pedagogical services (TPS) provided by pharmacists. The analysis excluded the dispensing of medicines from the Specialized Component of Pharmaceutical Assistance and used the “Reference Instrument for Pharmaceutical Services in Primary Care” to categorize the services. The results were adjusted by the National Broad Consumer Price Index for 2023 and presented in absolute and relative frequency, and rate per 100,000 inhabitants, based on the 2022 census. Results: In 2022 and 2023, 13,052,476 and 13,592,014 CAS and TPS procedures were performed, with rates of 6,427 and 6,693, respectively. Federal financing increased by 3.9% during this period (from R 49.5 million to R 51.5 million). CAS accounted for 96% of the allocated funds, while TPS represented 4%, distributed regionally as follows: southeast (33%), northeast (24%), north (21%), south (14%), and central-west (8%). Conclusion: Despite the increase in the number of procedures and federal funding, regional inequalities persist, and the funding remains modest compared to investment in the acquisition of medicines. Expanding access and the proper use of medicines are essential for the quality of health care.